Pharmacy practices and services in Myanmar: How stakeholders perceived and expect them? - Dar, Saw Thi; Kapol, Nattiya; Krichanchai, Sineenart; Poompruek, Panoopat (Science, Engineering and Health Studies, 2023)
Guidelines for Good Pharmacy Practice (GPP) were established by the Republic of the Union of Myanmar in 2017, aiming to implement them in neighborhood retail pharmacies by 2020. GPP encompasses a diverse range of stakeholders, and establishing mutual understanding among them is pivotal for the program's success. The purpose of this study was to explore stakeholders’ perspectives on pharmacy functions and their valuation of GPP. Employing a qualitative approach, this study assessed stakeholders’ opinions and expectations to depict current pharmacy services and practices. From July to September 2018, the study was carried out in three selected regions in Upper Myanmar. Sixty-two informants from verious stakeholder groups participated in one-on-one interviews, and content analysis was used to examine their responses. The findings revealed four key characteristics shaping the pharmacy landscape: (a) shared socially significant values between pharmacies and the general public, (b) diverse opinions amoung stakeholders regarding the effectiveness of pharmacy practices and services, (c) personal experiences of stakeholders with drug-related issues, and (d) a preference among stakeholders for a reductionist approach rather than a holistic one for improving pharmacy services. Overall, the study emphasized the varying and sometimes conflicting opinions among stakeholders, posing challenges to the rapid and successful adoption of GPP. Therefore, the establishment of a comprehensive understanding of the GPP is deemed crucial, specifically for the involved stakeholders.